Prediction of stress level in military submariners, based on physical conditioning and sleep quality variables - Maria Elisa Koppke Miranda; Pedro Moreira Tourinho; Guilhermo Brito Portugal; Ulisses Tirolo Taddei; Leonardo de-Souza Mendes Leal; Bruno Ferreira Viana; Priscila dos Santos Bunn; Rodrigo Gomes de Souza Vale (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The objective of the study was to predict the level of stress in military submariners based on physical fitness and sleep quality variables. Cross-sectional and correlational research, with a sample of 40 male submariners (28.70±3.98 years old). Body mass and composition data were analyzed (MCT), height, BMI, waist, body fat (%G), dominant handgrip (PMDom), cardiorespiratory fitness (VO2max), squats, sit-ups, relative power of lower limbs (PotRel MMII), stress (PSS-10), Epworth Sleepiness Assessment (ESE) and Pittsburgh Sleep Quality Index (PSQI). Overall, negative associations (p<0.05) were observed between VO2max and MCT, BMI, %BF, and waist; PotRel MMII and age and %BF; squat and %G; sit-up and MCT, BMI, %BF and waist; and finally, stress and VO2max and sit-up. Furthermore, positive associations (p<0.05) between BMI and MCT; %BF and MCT and BMI; waist and age, BMI, MCT, and %BF; squats and PMdom., VO2max and PotRel MMII; sit-ups and VO2max, PotRel LL and squats; ending with PSQI and stress. Furthermore, among the stress level prediction equation models developed, the equation Stress=15.92+1.538(PSQI)-0.497(VO2max)+0.188(Squat) met the proposed requirements, which is based on sleep quality, cardiorespiratory fitness, and number of squats.